Au@SiO2 core/shell nanoparticle assemblage used for highly sensitive SERS‐based determination of glucose and uric acid. (11th October 2013) - Quyen, Tran Thi Bich; Su, Wei‐Nien; Chen, Kuan‐Jung; Pan, Chun‐Jern; Rick, John; Chang, Chun‐Chao; Hwang, Bing‐Joe
<x xml:space="preserve">Abstract</x> The use of Au@SiO2 core/shell nanoparticle (NP) assemblage with highly sensitive surface‐enhanced Raman scattering (SERS) was investigated for the determination of glucose and uric acid in this study. Rhodamine 6G dye molecules were used to evaluate the SERS enhancement factor for the synthesized Au@SiO2 core/shell NPs with various silica shell thicknesses. The enhancement of SERS signal from Rhodamine 6G was found to increase with a decrease in the shell thickness. The core/shell assemblage with silica layer of 1–2 nm over a Au NP of ~36 nm showed the highest SERS signal. Our results show that the SERS technique is able to detect glucose and uric acid within wide concentration ranges, i.e. 20 ng/dL to 20 mg/dL (10−12–10−3 M) and 16.8 ng/dL to 2.9 mg/dL (10−11–1.72 × 10−4 M), respectively, with associated lower detection limits of ~20 ng/dL (~1.0 × 10−12 M) and ~16.8 ng/dL (~1.0 × 10−11 M). Our work offers a low‐cost route to the fabrication of agile sensing devices applicable to the monitoring of disease progression. Copyright © 2013 John Wiley & Sons, Ltd.